Economic Literacy amongst Business Students in Kathmandu Valley - Sharma, Susmita (Nepalese Journal of Economics, 2024)
This study examines the economic literacy amongst business students in Kathmandu Valley. Economic literacy is the dependent variable. The selected independent variables are investment, saving, economic education, expenditure and parent education. The primary source of data is used to assess the opinions of the respondents regarding economic literacy amongst business students. The study is based on primary data with 140 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors on economic literacy amongst business students in Kathmandu Valley. The study showed that parent education has a positive impact on economic literacy which indicates that higher the level of parent education, higher would be the economic literacy of students. Moreover, economic education has a positive impact on economic literacy indicating that increase in economic education leads to increase in economic literacy. Similarly, investment has a positive impact on economic literacy. This implies that increase in investment by business students leads to increase in economic literacy. The results of the study also revealed that saving has a positive impact on economic literacy. This implies that increase in saving leads to increase in economic literacy. Similarly, expenditure has a positive impact on economic literacy indicating that good education of expenditure leads to increase in economic literacy.